Depression and tetrahydrobiopterin: the folate connection. - Coppen, A; Swade, C; Jones, SA; Armstrong, R; Blair, J; Leeming, R (1989)
Total biopterin, neopterin and creatinine were measured in spot urine samples from affective disorder patients on lithium therapy and control subjects. Folic acid was also measured in plasma in a sample of the patients. The mean neopterin: biopterin ratio was significantly higher in the 76 patients (3.2 +/- 0.5) than in the 61 controls (1.8 +/- 0.1). In female patients biopterin levels were significantly lower than in controls. In the control groups there was a significant correlation between the molar concentration of neopterin and biopterin. No such correlation was found in the patients. These data indicate that tetrahydrobiopterin (BH4) biosynthesis is reduced in this group. A significant positive correlation was found between plasma folate and urinary biopterin. It is suggested that folate deficiency may impair the synthesis of BH4, a cofactor essential for the synthesis of 5-HT and other monoamines that are involved in the pathogenesis of affective disorders.